Ստամոքսի և աղիների խոցային հիվանդությունները միջնադարյան հայկական բժշկարաններում - Հայրապետյան, Հասմիկ («Նաիրի» հրատ.)
В статье дается сравнительный анализ взглядов восточных и армянских средневековых врачей относительно этиологии, патоге-неза, клинической симптоматологии и лечения язвенной болезни желудка и кишечника. This article provides a comparative analysis of the views of ancient, Arab and medieval Armenian physicians regarding the etiology, pathogenesis, clinical symptomatology and the treatment of stomach and intestine peptic ulcers.
Keywords: Միջնադարյան բնագիտություն; Բժշկություն